P131 LOW DOSES OF ADVANCED GLYCATION END–PRODUCTS AND FRUCTOSILATION PRODUCTS PROMOTES PREMATURE CELL DEATH OF HUMAN CARDIAC CELLS EXPOSED TO DOXORUBICIN VIA ACTIVATION OF NLRP3, MYD88 AND P53 DOWNREGULATION. (18th May 2022) - Quagliariello, V; Paccone, A; Iovine, M; Buccolo, S; Maurea, N
Abstract: Introduction: Advanced glycosylation end–products (AGEs) are non–enzyme, protein glycosylation products caused by glucose–induced metabolic disorder, and play an important role in aging, cancer, metabolic syndrome and cardiovascular diseases. Purpose: We aimed to assess whether AGEs and fructosilation products, such as methylglyoxal (MG) and N–carboxymethyllysine (N–CML) could increase susceptibility to cell damages induced by doxorubicin Methods Human cardiomyocytes were pre–exposed for 24h with low doses (50 mmol/L) of methylglyoxal (MG) or N–carboxymethyllysine (N–CML). After, cells were exposed to subclinical concentration of doxorubicin (at 100 and 200 nM) for 48 and 72h. After the incubation period, we performed the following tests: determination of cell viability, through analysis of mitochondrial dehydrogenase activity, study of lipid peroxidation (quantifying cellular Malondialdehyde and 4–hydroxynonenal), intracellular Ca2+ homeostasis. Moreover, pro–inflammatory studied were also performed (activation of NLRP3 inflammasome; expression of peroxisome proliferator–activated receptor–α; mTORC1 Fox01/3a; transcriptional activation of p65/NF–κB and secretion of cytokines involved in cardiotoxicity (Interleukins 1β, 8, 6). Expression of p53 was also performed through western blot method Results: Pre–exposure to methylglyoxal (MG) but especially to N–carboxymethyllysine (N–CML) increase cell mortality to doxorubicin of 48–53% compared to control. Pre–exposure to N–CML promotes premature death of cardiomyocytes to doxorubicin through NLRP3–driven pathways. Notably, MG and N–CML increased significantly the cardiotoxicity through NLRP3 inflammasome, Myd88 myddosome and cytochrome C–mediated apoptosis. Pre–exposure to N–CML and MG increase the secretion of interleukin–6 that increase cell apoptosis through a paracrine and autocrine mechanism. Induction of IL–6 reduces the expression of p53 resulting in the induction of the apoptotic process. Conclusion: These observations suggest that AGEs and fructosilation producs promotes premature cardiotoxicity of human cardiac cells exposed to doxorubicin by activation of NLRP3, Myd88–related pathways and downregulation of p53.